Longitudinal Circulating Tumor DNA–Guided Resistance Analysis During Second-Line Osimertinib Treatment - J.W. Tijmen van der Wel, MD; Merel Jebbink, MD; Vincent van der Noort, PhD; Ferry Lalezari, MD, PhD; Daan van den Broek, PhD; Gerrina Ruiter, MD, PhD; Jacobus A. Burgers, MD, PhD; Paul Baas, MD, PhD; Anne S.R. van Lindert, MD; Eva E. van der Wall, MD; Lisanne E.A. Kastelijn, MD, PhD; Marrit Vermeulen, BSc; et al. (JTO Clinical and Research Reports, 2025)
Introduction: In osimertinib-treated EGFR mutation (EGFRm)–positive NSCLC, resistance inevitably occurs. Early resistance mechanism (RM) detection by circulating tumor DNA (ctDNA) in plasma and consecutive targeted treatment may delay progressive disease (PD). In this multicenter prospective study, we evaluated the detection rate and time interval of RM emergence in plasma ctDNA before radiologic PD. Methods: Patients with EGFRm–positive NSCLC, treated with second- or third-line osimertinib, underwent computed tomography of the thorax and ctDNA analysis (Roche AVENIO expanded panel, research use only [Roche Sequencing Solutions, Roche, Basel, Switzerland]) at baseline and every 8 weeks for response evaluation and EGFRm and RM detection. If MET amplification preceded PD, crizotinib was to be added to osimertinib. Other RMs were monitored but not acted on. After PD, patients underwent a tumor biopsy. Results: Of the 21 evaluable patients, 18 had detectable ctDNA at baseline. In patients with undetectable ctDNA at baseline, ctDNA remained undetectable during treatment. In the 17 out of 18 (94%) patients with detectable ctDNA, PD occurred. In seven out of 21 patients (33%), the EGFRm variant allele frequency increase preceded radiologic PD with a median interval of 9 weeks (range 7–34). In seven out of 21 patients (33%), at least one RM was detected before PD, and the median interval was 14 weeks (range 7–34). Three had one or more RM in ctDNA at baseline. No MET amplification was observed, and treatment with crizotinib was not initiated in any patient. After PD, 16 biopsies were obtained. Five confirmed the RM detected in plasma, five biopsies revealed additional RMs, and six harbored no RM. Conclusions: In 33% of patients treated with second- or third-line osimertinib, RMs in plasma preceded PD by a median of 14 weeks, suggesting an opportunity for early treatment adjustment, potentially extending tyrosine kinase inhibitor treatment duration.